Diabetic Myonecrosis: An Atypical Presentation - José Hernán Martínez; Oberto Torres; Michelle M. Mangual García; Coromoto Palermo; María de Lourdes Miranda; Eva González; Ignacio Chinea Espinoza; Ivan Laboy; Mirelis Miranda; Kyrmarie Dávila; Rafael Tirado; Mildred Padilla (Case Reports in Endocrinology)
Diabetic myonecrosis is a frequently unrecognized complication of longstanding and poorly controlled diabetes mellitus. The clinical presentation is swelling, pain, and tenderness of the involved muscle, most commonly the thigh muscles. Management consists of conservative measures including analgesia and rest. Short-term prognosis is good, but long-term prognosis is poor with most patients dying within 5 years. Failure to properly identify this condition will expose the patient to aggressive measures that could result in increased morbidity. To our knowledge this is the first case reported in which there was involvement of multiple muscle groups including upper and lower limbs.